Contribution of aged organic carbon to suspended particulate organic carbon in the western equatorial Indian Ocean - Kang, Sujin; Zhang, Hailong; Ding, Yang; Zhao, Meixun; Son, Yeong Baek; Son, Purna; Rho, Tae Keun; Kang, Dong-Jin (Frontiers in Marine Science, 2024)
We investigated dual carbon isotopes within the vertical water column at sites 67-1 and 67-2 of the western equatorial Indian Ocean to determine the source and age of particulate organic carbon (POC) and thus evaluated the contributions of modern and fossil (aged) POC.The concentration of POC ranged from 7 to 47.3 μgC L -1 , δ 13 CPOC values ranged from -31.8 to -24.4‰, and Δ 14 CPOC values ranged from -548 to -111‰. Higher values of δ 13 CPOC and Δ 14 CPOC near the surface indicated an influence of autochthonous POC, whereas decreasing trends toward the bottom suggested a contribution of aged OC sources to the total POC pool.The contribution of fossil POC was lower near the surface, accounting for only 12% and 6% of the total POC at sites 67-1 and 67-2, respectively; however, in the deeper layers below 1,000 m, the contribution of fossil POC increased to 52% and 44% of the total POC at the two sites.Mechanisms for the increased contributions of fossil OC within deeper POC include the inflow of ancient OC from sediments resuspended near slopes, the adsorption of old dissolved organic carbon in deep water masses, and the impact of aged OC that may originate from hydrothermal sources. This study highlights the importance of aged OC in the carbon cycle of the equatorial Indian Ocean.